Análisis metagenómico de las rutas de degradación de compuestos xenobióticos por microorganismos de islas de recursos del caribe colombiano - Mediorreal Niño, Adriana Paola (Universidad Antonio Nariño, 2025)
The metagenomic analysis of microbial communities in resource islands of the Colombian Caribbean revealed their potential for xenobiotic compound degradation, highlighting their relevance for bioremediation applications. Soils associated with nurse trees under different microenvironmental conditions were analyzed, identifying 702 genes related to degradation pathways, of which 300 showed confirmed activity.